Pengembangan Modul Radiator Trainer untuk Meningkatkan Hasil Belajar Mahasiswa Jurusan Teknik Mesin UNESA - Sudirman Rizki Ariyanto; I Made Arsana; Riyadlul Ulum (Department of Mechanical Engineering Education, 2019)
This study aims to develop modules as a learning media to facilitate the students in their learning of heat transfer. The study also tries to obtain an overview of the developed modules' feasibility. This is development research which aim is to produce a learning module. This module was tested in the Department of Mechanical Engineering at Surabaya State University. Fifteen students were randomly selected as respondents. The stages carried out in the development of this module comprise of the following phases: defining, designing, and development. Analysis of the data obtained from students' learning outcome after attending the study using the